(3GdebGdI GdaGVdjI (B( (3GdSehe (B)s - (3ehSi Hf YHjO Gddg Hf ejehf GdbQWHj, CHh YeQGf,J (B601 (3g` s
(3ChdgG (B:s
(3bO TgQ ai GYUGQfG hai EbdjefG gPG Hd ai YOI CbGdje SjQI ehdGfG GdbGVi NdO Gddg CjGeg hfMf fQi Cf fVY ebGdI UZjQg GdMLe LjOI GddaX LGeYI deG jHGOQ Hg GdedShYjf ef GdJOHjQ s
(3BNQgG (B:s
(3gPG GdbOQ bO QBg Gdeedhc cGajkG hdYdg hGab GdZQV Ef TGA Gddg JYGdi s
(3CdagG HfGA Ydi WdH GdbGVi GdaGVd YHO GdQMje Hf Ydi GdHjSGfis
(3GfXQ agQS GdWH HQbe (B118 (3HYfhGf QSGdI ai GdedShYjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B241 s
Keywords: (3GdWHs